2013
DOI: 10.1177/1933719113488455
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Reduces Myometrial Infiltration, Uterine Hyperactivity, and Stress Levels and Alleviates Generalized Hyperalgesia in Mice Induced With Adenomyosis

Abstract: In an effort to search for novel therapeutics for adenomyosis, we sought to determine whether treatment with epigallocatechin-3-gallate (EGCG) would suppress the myometrial infiltration, improve pain behavior, lower stress level, and reduce uterine contractility in a mice model of adenomyosis. Adenomyosis was induced in 28 female ICR mice neonatally dosed with tamoxifen, while another 12 (group C) were dosed with solvent only, which served as a blank control. Starting from 4 weeks after birth, hot plate test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 62 publications
2
52
0
Order By: Relevance
“…33,34 Of relevance to our study, high levels of uterine contractility have been shown to be associated with dysmenorrhea in women with symptomatic adenomyosis, in a context of high stress levels and pain. 35 Ongoing studies in our laboratories are investigating the effect of stress on the pain threshold and the influence of the brain-gut axis in these changes.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Of relevance to our study, high levels of uterine contractility have been shown to be associated with dysmenorrhea in women with symptomatic adenomyosis, in a context of high stress levels and pain. 35 Ongoing studies in our laboratories are investigating the effect of stress on the pain threshold and the influence of the brain-gut axis in these changes.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 We have previously shown that mice with induced adenomyosis exhibit increased uterine hyperactivity, general hyperalgesia, and elevated plasma corticosterone levels. 9,10,20 We have also shown that treatment with valproic acid, a histone deacetylase (HDAC) inhibitor, is efficacious in improving generalized hyperalgesia resulting from induced adenomyosis in mice. 20 Treatment with levo-tetrahydropalmatine, an analgesia, and andrographolide, an NF-kB inhibitor, can retard myometrial infiltration, reduce uterine contractility, and alleviate generalized hyperalgesia in mice with induced adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, we have recently shown that treatment with epigallocatechin-3-gallate (EGCG), a major component of green tea, dose dependently suppressed myometrial infiltration, improved generalized hyperalgesia, reduced uterine contractility, and lowered plasma corticosterone levels. 10 Based on the same experiment as we reported recently, 10 we sought to determine in this study as whether the induction of adenomyosis would cause any changes in the NRM, and, if so, whether the change would correlate with the documented change in hotplate latency in mice with or without adenomyosis. We also sought to determine, as a sequel to the study previously reported, 10 whether the treatment of EGCG would rectify the change in NRM resulting from adenomyosis induction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations